Inhibition of integrin alpha v/beta 5 mitigates the protective effect induced by irisin in hemorrhage - Lijiang Wang; Supaporn Kulthinee; John Slate-Romano; Thomas Zhao; Hamsa Shanmugam; Patrycja M Dubielecka; Ling X. Zhang; Gangjian Qin; Shougang Zhuang; Y. Eugene Chin; Ting C. Zhao (Elsevier, 2023)
Introduction: Irisin plays an important role in regulating tissue stress, cardiac function, and inflammation. Integrin αvβ5 was recently identified as a receptor for irisin to elicit its physiologic function. It remains unknown whether integrin αvβ5 is required for irisin's function in modulating the physiologic response to hemorrhage. The objective of this study is to examine if integrin αvβ5 contributes to the effects of irisin during the hemorrhagic response. Methods: Hemorrhage was induced in mice by achieving a mean arterial blood pressure of 35-45 mmHg for one hour, followed by two hours of resuscitation. Irisin (0.5  μg/kg) was administrated to assess its pharmacologic effects in hemorrhage. Cilengitide, a cyclic Arg-Gly-Asp peptide (cRGDyK) which is an inhibitor of integrin αvβ5, or control RGDS (1 mg/kg) was administered with irisin. In another cohort of mice, the irisin-induced protective effect was examined after knocking down integrin β5 with nanoparticle delivery of integrin β5 sgRNA using CRSIPR/Cas-9 gene editing. Cardiac function and hemodynamics were measured using echocardiography and femoral artery catheterization, respectively. Systemic cytokine releases were measured using Enzyme-linked immunosorbent assay (ELISA). Histological analyses were used to determine tissue damage in myocardium, skeletal muscles, and lung tissues. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) was carried out to assess apoptosis in tissues. Results: Hemorrhage induced reduction of integrin αvβ5 in skeletal muscles and repressed recovery of cardiac performance and hemodynamics. Irisin treatment led to significantly improved cardiac function, which was abrogated by treatment with Cilengitide or knockdown of integrin β5. Furthermore, irisin resulted in a marked suppression of tumor necrosis factor-α (TNF-α) and interleukin-1 (IL-1), muscle edema, and inflammatory cells infiltration in myocardium and skeletal muscles, which was attenuated by Cilengitide or knockdown of integrin β5. Irisin-induced reduction of apoptosis in the myocardium, skeletal muscles, and lung, which were attenuated by either the inhibition of integrin αvβ5, or knockdown of integrin β5. Conclusion: Integrin αvβ5 plays an important role for irisin in modulating the protective effect during hemorrhage.